2017
DOI: 10.1074/jbc.m117.793760
|View full text |Cite
|
Sign up to set email alerts
|

NK3 homeobox 1 (NKX3.1) up-regulates forkhead box O1 expression in hepatocellular carcinoma and thereby suppresses tumor proliferation and invasion

Abstract: Hepatocellular carcinoma (HCC) is the leading cause of cancer-related mortality in China, and the molecular mechanism of uncontrolled HCC progression remains to be explored. NK3 homeobox 1 (), an androgen-regulated prostate-specific transcription factor, suppresses tumors in prostate cancer, but its role in HCC is unknown, especially in hepatocellular carcinoma. In the present study, the differential expression analyses in HCC tissues and matched adjacent noncancerous liver tissues revealed that NKX3.1 is freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…NKX3-1 negatively regulates the PI3K-AKT pathway to suppress tumor growth, and heterozygous deletions of NKX3-1 and PTEN cause prostate adenocarcinomas in mice ( Abate-Shen et al, 2003 ). Additionally, NKX3-1 functions as a tumor suppressor in hepatocellular carcinoma ( Jiang et al, 2017a ). In our analysis, increased NKX3-1 expression is strongly associated with poor overall survival ( P = 1.74 × 10 −4 ), and consistently higher expression is also found in prostate adenocarcinoma ( Fig.…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…NKX3-1 negatively regulates the PI3K-AKT pathway to suppress tumor growth, and heterozygous deletions of NKX3-1 and PTEN cause prostate adenocarcinomas in mice ( Abate-Shen et al, 2003 ). Additionally, NKX3-1 functions as a tumor suppressor in hepatocellular carcinoma ( Jiang et al, 2017a ). In our analysis, increased NKX3-1 expression is strongly associated with poor overall survival ( P = 1.74 × 10 −4 ), and consistently higher expression is also found in prostate adenocarcinoma ( Fig.…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…ChIP assays were performed with SMMC-7721 and Hep3B cells as previously described. 33 Rabbit anti-EGR1 antibody (SC-189, Santa Cruz Biotechnology) or rabbit IgG were used to immunoprecipitate DNA-containing complexes. The isolated DNA samples were subjected to PCR analyses.…”
Section: Chromatin Immunoprecipitation Assay (Chip)mentioning
confidence: 99%
“…Tumor proliferation and apoptosis plays an important role in the occurrence and development of HCC [ 4 ]. The researches have demonstrated that HCC proliferation and apoptosis are closely related to abnormal expression of oncogenes and tumor suppressor genes [ 5 , 6 ]. Therefore, identification of novel diagnostic markers and therapeutic targets in HCC are urgently needed.…”
Section: Introductionmentioning
confidence: 99%